Avicennia marina Mangrove Plant Mediated Selenium Nanoparticles and Their Therapeutic Activity Against Oral Pathogens and Other Biological Properties - Kamala, Kannan; Sivaperumal, Pitchiah; Ganapathy, Dhanraj (UI Scholars Hub, 2024)
In the last few decades nanoparticles are widely used in the control of many pathogenic bacteria, fungi, viruses, and cancer growth both in-vitro and in-vivo. A marine plant of Avicennia marina is widely used in traditional medicine for diabetes, inflammation and skin diseases. Objective: In general Avicennia marina has been used as a traditional medicine to treat various diseases and it has shown significant inhibition against various pathogen and the formation of free radicals. Also, the plant A.marina mediated selenium nanoparticles has therapeutic activity has promising to develop biocompatible new cost effective treatment for various oral diseases. Methods: In the present investigation, we have used A.marina for the green synthesis of SeNPs (selenium nanoparticles) and it was characterized for its surface Plasmon resonance by UV-Vis spectroscopy, morphology analyzed by SEM, elements determined by EDX spectroscopy. Further, functional groups of the SeNPs were determined by FT-IR. Results: The prepared nanoparticles were spherical-shaped withsize ranging 20-60 nm. Subsequent evaluations focused on the antimicrobial potential of the synthesized nanoparticles against common oral pathogens responsible for dental cavities and other oral diseases, encompassing Streptococcus intermedius, Prophyromonas gingivalis, Campylobacter rectus, Fusobacterium nucleatum and Treponema denticola. The SeNPs derived from the marine plant demonstrated both cytotoxic effects and significant zones of inhibition against these oral pathogens. Additionally, these nanoparticles exhibited promising capabilities in scavenging DPPH radicals and displayed anti-inflammatory properties. Conclusion: In light of above-mentioned findings, it can be deduced that SeNP’s synthesized through the mediation of A. marina hold substantial promise for diverse pharmaceutical and medical applications.